2019
DOI: 10.1029/2018wr024615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sand Addition and Bed Flushing on Gravel Bed Surface Microtopography and Roughness

Abstract: Gravel riverbeds naturally present a range of sediment size that can span several orders of magnitude. However, fine sediment (i.e., size <2 mm) additions affect sediment transport and are potentially harmful to the river ecology. Limited research has been done to understand the effects of sand addition on gravel bed topography. For this study, we conducted flume experiments testing the effectiveness of topography remote sensing to measure the response of a water‐worked gravel bed to varying sand additions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Increased channel energy conditions likely occurred due to pulse‐derived increases in local channel slope, bed fining from sediment pulse fines draped over coarser bed sediment, and/or pool and bed topography filling. Previous studies have also demonstrated that fine sediment draped over, or infiltrating into, a coarser bed can result in a smoother bed with lower bed roughness (Bertin & Friedrich, 2019), increase near‐bed velocities, and even enhance bed mobilization in some contexts (Venditti et al, 2010). Sediment pulses from other dam removals have also been associated with channel fining, including higher‐gradient removals such as those on the Elwha River (East et al, 2018) and in lower‐gradient channels (Harrison et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Increased channel energy conditions likely occurred due to pulse‐derived increases in local channel slope, bed fining from sediment pulse fines draped over coarser bed sediment, and/or pool and bed topography filling. Previous studies have also demonstrated that fine sediment draped over, or infiltrating into, a coarser bed can result in a smoother bed with lower bed roughness (Bertin & Friedrich, 2019), increase near‐bed velocities, and even enhance bed mobilization in some contexts (Venditti et al, 2010). Sediment pulses from other dam removals have also been associated with channel fining, including higher‐gradient removals such as those on the Elwha River (East et al, 2018) and in lower‐gradient channels (Harrison et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Six sand transport rates were obtained for each flow discharge tested, the results were then interpolated to determine the relationship between sand transport and water discharge. This approach of sand addition differs from previous studies (e.g., Bertin & Friedrich, 2019;Perret et al, 2018), where the sand was fed at a constant rate, irrespective of the flow discharge. A total of ∼145 and ∼281 kg of sand was added during each 1/1 and 1/3, 3/1 experimental run, respectively.…”
Section: Experimental Facilitiesmentioning
confidence: 87%
“…Mobile sediment was placed in the test section (Figure 1). To keep the mobile sediment horizontally aligned with the height of the artificial bed upstream and downstream of the test section, the vertically adjustable table underneath the test section was manually leveled upwards with screw jacks, a design that has been successfully used in previous gravel‐bed studies (Bertin & Friedrich, 2019; Heays et al., 2014).…”
Section: Experimental Design and Methodsmentioning
confidence: 99%
“…Sediment reworking on the beach and nearshore due to waves and currents traduces by the formation of topographic complexity (herewith generally called roughness), such as sedimentary bedforms. These topo-morphological features are the imprint of the processes that shaped them, and, as such, measuring bedforms can provide meaningful information on hydrodynamic forces [6][7][8][9][10]. Besides, bedforms are roughness elements that modify the flow and dissipate energy [11,12].…”
Section: Introductionmentioning
confidence: 99%